Rediscovery of Phalotris concolor (Serpentes: Dipsadidae: Elapomorphini) - Mario Ribeiro Moura; Henrique Caldeira Costa; Renata Magalhães Pirani (Zoologia (Curitiba), 2013)
Phalotris concolor Ferrarezzi, 1994 is a poorly known species described on the basis of a single female from municipality of Cristália, state of Minas Gerais, Brazil. Based on two recently collected specimens, we expand the knowledge of P. concolor with new morphological data, including the description of its hemipenis and color in life. A summary of comparative data between species of the P. nasutus group is present to aid the identification of new specimens. The new findings are important for a better understanding of the taxonomy of Phalotris.